Self‐Triggered Impulsive Synchronization Control of Multi‐Agent Systems With Sensing Delays and Deception Attacks - He, Jiangyan; Guo, Xing; Ji, Lianghao; Chen, Zili (International journal of robust and nonlinear control, 2025)
ABSTRACT The paper explores the mean‐square bounded synchronization problem of multi‐agent systems (MASs) in the presence of lumped factors, including stochastic interferences, edge‐based deception attacks, and sensing delays. To tackle this challenging problem, a new secure delayed impulsive control protocol is proposed, in which the agents receive erroneous signals from their neighbors due to edge‐based deception attacks on the transmission channel. Two self‐triggered strategies, static and dynamic, are designed to drive the impulsive control, which is correlated with the sensing delay time, the probability of deception attacks occurring, as well as the intensity of the attack signals. Further, we have introduced a boundary floating function to mitigate the impact of external uncontrollable factors on the bounded synchronization of MASs under the dynamic self‐triggered strategy. Compared with previous studies, this strategy takes into account the natural disturbances and exhibits greater robustness. Some criteria for the mean‐bounded synchronization of MASs are obtained under the designed control protocol by applying the Lyapunov stability theory, Itô formula, and Gronwall‐Bellman inequality. Finally, these conclusions are verified by simulation with two examples.